Employing generative AI applications in learning: A factor analysis of motivations and effects among Moroccan university students - Nadif, Bendaoud; Zemrani, Mohammed; Ait Hammou, Brahim; Mansour, Salah-Eddine; Fakhrou, Abdulnaser; Bouih, Abdelouahed (American Journal of STEM Education, 2026)
This study seeks to understand the nature of the use of generative artificial intelligence (GenAI) applications among Moroccan university students, by investigating the motivations for use and the effects of this use, by adopting the structural equation modeling technique using the partial least squares method (PLS-SEM) using the SmartPLS version 4 program, to analyze the study data collected through a scale prepared for this study and applied to a random sample of (206) male and female students from different Moroccan universities. After verifying the reliability of the proposed model, the study reached a set of results: Study pressure is the main motivation for using generative artificial intelligence applications among students, while the effect of time pressure and the search for quality and rewards was less significant.